PROBLEMS AND SOLUTIONS TO ENGLISH TEACHING - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi, (Журнал иностранных языков и лингвистики, 2023)
You must be able to contribute to the achievement of the practical, cultural, and educational goals of learning a foreign language. By teaching materials, we mean the materials that the teacher can use to help students learn a foreign language through visual or auditory perception.